Myelin Oligodendrocyte Glycoprotein Antibody (MOG-IgG)-Positive Optic Perineuritis. (2nd January 2020) - Lopez-Chiriboga, A. Sebastian; Van Stavern, Gregory; Flanagan, Eoin P.; Pittock, Sean J.; Fryer, Jim; Bhatti, M. Tariq; Chen, John J.
ABSTRACT: Optic perineuritis can be a manifestation of infectious and systemic inflammatory disorders, but the majority of cases are idiopathic. Myelin oligodendrocyte glycoprotein (MOG)-IgG-positive optic neuritis has been reported to be associated with optic nerve sheath enhancement. This report describes two MOG-IgG patients with clinical, radiological and therapeutic response consistent with optic perineuritis. MOG-IgG may account for many cases of previously described idiopathic optic perineuritis. Vision loss with optic nerve sheath enhancement on MRI should prompt testing for MOG-IgG.